A Preliminary Study of Analysis and Characterization of Briquettes Quality on Asphalt Bitument from Buton Island as Alternative Fuel - Arisona .; Anas M.; Musta C. (Jurnal Aplikasi Fisika, 2014)
In this study, the material  used is asphal bitument then made briquettes weighing 10 gram in each sample. In making the briquettes used a cylindrical mod with a diameter of 2.5 cm and a height of 7 cm. After compactioned the briquettes produced dried first. Drying of briquetttes made using free air during 4 days to reduce the water content contained in the briquettes. Furthermore, the heat test and proximat analysis (i.e : analysis of water content, ash content, volatile matter, fixed carbon, and density). Calorific test and proximate analysis aims to determine the  quality of asphal bitument briquettes that will be used as a fuel alternative. This results of this study indicate that the asphalt briquettes have analyzed proximet variation i.e.: water content between 1.23% -7.26% ; volatile matter : 16,797%-32,02% ; ash content : 48.96%-61.35% ; fixed carbon : 11.76%-33.36 ; and density : 1,22 g/cm3-1.92 g/cm3. Asphalt briquettes obtained has a calorific value variation between 1902.39 kcal/kg- 3407.82 kcal/kg, with the largest being  the calorific  value of  cashew charcoal with variation of 30 %. This provides an initial indication for the use of asphalt bitument briquettes as alternative fuel and also provide information that adhesive such as cashew charcoal can be used as aggregate  to strengthen the adhesion of  asphalt on the pavement layers.